Sustainable Development Goals Indicators for Finland : Statistical Annex of the Finnish Voluntary National Report 2025 on the Implementation of Agenda 2030 - (:unkn) unknown (Statistics Finland, 2025)
Progress towards implementing the 2030 Agenda for sustainable development is followed and reviewed by using a set of global indicators. The global Sustainable Development Goals (SDGs) indicator framework was first agreed upon by the United Nations Statistical Commission and adopted by the General Assembly in 2017. It consists of over 231 unique indicators and it aims to ensure a balance across the goals and targets of the 2030 Agenda for sustainable development. This report provides, in the form of statistics and graphics, key data for reviewing the progress made in implementing the 17 Sustainable Development Goals and 169 targets.
Keywords: tilastot; kestävä kehitys; yhteiskunta